Experimental study on unsymmetrically loaded deep beams subjected to fires - Alessandro, James (2019)
Extensive studies have been conducted to evaluate structural robustness in the presence of fire since the collapse of World Trade Centre (WTC) buildings, New York. However, only limited research focused on the behaviour of reinforced concrete (RC) deep beams in fire conditions. Furthermore, no existing fire design code could be found to determine the capacity of deep beams subjected to elevated temperatures. For deep beams consisting of entirely D-regions, shear capacity governs the performance. Meanwhile, the standard fire design guidelines are mostly based on flexural capacity of beams. Only EN 1992-1-2 (2004) recommends using the universal design approach for flexural capacity to determine the shear capacity, but this recommendation has yet to be verified. Besides, the present fire design codes are only applicable to shallow RC beams where Bernoulli’s hypotheses are valid. Therefore, investigations into the structural behaviour of deep beams under fires are carried out through experimental and analytical programmes. The analytical model is developed by modifying direct strut-and-tie models (STMs) at ambient temperature that is recommended by EN 1992-1-1 (2004) and ACI 318 (2014). In general, three unequally-loaded deep beams were tested at elevated temperatures. The primary aim of the tests is to assess the combined effect of load configuration and high temperature in failure modes, crack patterns, and responses of RC deep beams. The results from this study show that fire is critical in reducing the strength capacity of deep beams which leads to failure of the beams by degrading the strength of concrete and steel reinforcement. The crack patterns and failure modes of the fire-exposed beams are found to be similar to those of corresponding beams at ambient temperatures, except failure modes of deep beams when subjected to large load inequality. The crack patterns are fully developed in the higher loaded shear span. This, in turn, results in diagonal splitting shear failure at this span. The lighter loaded shear span is less critical as load intensity keeps increasing. For large load inequality, large flexural cracks cause a reduction of concrete area at the top strut. Instead of common diagonal splitting failure, combined effect of fire and flexural cracks leads to shear compression failure in the concrete top strut. A direct STM incorporating the effect of fire and loading mechanism is proposed to determine the failure mode and load-carrying capacity of deep beams. It is derived from the EN 1992-1-1 (2004)- and ACI 318 (2014)- recommended STM at ambient temperature by inclusion of material properties at average elevated temperatures. The experimental results obtained are utilised to validate the heat transfer model of deep beams and the proposed STMs. The proposed STMs were found to have a good correlation with the crack patterns and the failure time of the test results.